Evaluation and influencing factors of ecological resilience in tourism villages from farmers’ perspectives: a case study of Chinese minority settlement areas - Wu, Jilin; Yang, Yimin; Zuo, Jinyou; Cao, Qingqing; Guo, Derong; Liu, Shuiliang (Frontiers in Environmental Science, 2024)
Rural social-ecological systems have been significantly impacted by the development of rural tourism, creating substantial challenges for the synergistic development of rural ecological restoration and agricultural workers' household livelihoods. In alignment with the United Nations Decade on Ecosystem Restoration action plan, it is crucial to understand the ecological resilience of tourism villages from the perspective of farmers to achieve sustainable development. Questionnaires and semi-structured interviews were conducted in this study to gather livelihood data from farmers in tourism villages in Xiangxi, China, a region primarily inhabited by ethnic minorities. A measurement index system for the ecological resilience of rural tourism was constructed based on the three dimensions: pressure, state, and response. A comprehensive index method was employed for quantitative evaluation, and influencing factors were analyzed using an obstacle model. The results show that farmers' livelihoods can be divided into four types: tourism-led, labor-led, agriculture-led, and part-time tourism-based. Their ecological resilience indices are 0.4516, 0.4177, 0.4001, and 0.4590, respectively, representing an overall intermediate level. There are differences in various indices for different livelihood types, with the highest stress index observed in labor-led farmers (0.1655), the highest state index in agriculture-led farming households (0.1585), and the highest response index in tourism-led farming households (0.1766). Common obstacles to the ecological resilience of farmers and their villages include the number of family members engaged in tourism work, the area of forest land, and the farmers' understanding of ecological policies affecting them.Additionally, core family members' education levels and the area of homesteads emerged as important obstacle factors. Based on these research findings, recommendations are proposed to enhance the ecological resilience of rural farmer households in the tourism villages of ethnic minority areas. The aim is to provide valuable case studies for promoting the sustainable development of rural tourism in underdeveloped regions worldwide.